The relation between the soteropolitana press with the coup of 1889: an analysis of journalistic discourses on the proclamation of the republic - Fonseca, Matheus Berlink (Em Perspectiva, 2017)
This paper analyzes the journalistic discourses used by the newspapers that circulated in the city of Salvador during the first fortnight after the Proclamation of the Republic of Brazil. Seeking to understand the political position of these newspapers from their political orientations. The main sources used were newspapers, as well as police inquiries. The methodology used was the analysis of the discourse and the dialogue with the specific bibliography on the theme of the Proclamation of the Republic as the works of Jose Murilo de Carvalho for Rio de Janeiro and Wlamyra Albuquerque for Bahia. The research revealed that the local discourse was biased towards republicanism, which influenced the diffusion of the events of the new system of government in the soteropolitana press.